THE IMPLEMENTATION OF DIFFERENTIATED LEARNING TO DEVELOP COLLABORATION SKILLS AMONG FOURTH GRADE STUDENTS AT ELEMENTARY SCHOOL BERBEK NGANJUK IN SOCIAL STUDIES - Wahida, Siska Nur; Siswanto, M. Bambang Edi (Four Son Scholarship, 2025)
This study aims to gain a deeper understanding of the application of differentiated learning and its impact on the development of students' collaborative skills. The research method used is qualitative and a descriptive approach. The research subjects or informants were all fourth-grade students of Elementary School (SDN) Berbek Nganjuk. Research data were obtained through observation, interviews, and documentation. The results of the study indicate that the application of differentiated learning in social studies as an effort to develop the collaborative skills of fourth-grade students of SDN Berbek has a role in developing students' collaborative skills. Supported by research results that show developments from the first meeting to the second meeting. It was found that more than half of the number of students fell into the collaborative category, then less than half of the number of students fell into the very collaborative category, and a small number of students fell into the fairly collaborative category. The most visible development was when improvements in interaction and collaboration between students during learning illustrated that the application of differentiated learning had a direct positive impact on the development of their social skills as well